1984
DOI: 10.1002/hep.1840040222
|View full text |Cite
|
Sign up to set email alerts
|

Franco-Belgian Cooperative Study of Ursodeoxycholic Acid in the Medical Dissolution of Gallstones: A Double-Blind, Randomized, Dose-Response Study, and Comparison with Chenodeoxycholic Acid

Abstract: A double-blind randomized, multicenter study was carried out to determine the efficacy and safety of ursodeoxycholic acid (UDCA) at 4 doses of 2.1 to 16.2 mg X kg-1 X day-1, and chenodeoxycholic acid (CDCA) at the dose of 16.9 mg X kg-1 X day-1, in 197 patients treated for up to 1 year for radiolucent gallstones in functioning (opacified) gallbladders. There was confirmed complete dissolution in 5.9% of patients receiving UDCA at the dose of 2.1 mg X kg-1 X day-1, 18.9% in those receiving 4.2, 28.9% in those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…Therefore, it is likely that UDCA also reduces biliary output of plant sterols and cholestanol. Since UDCA has no effects on lipoprotein metabolism (16,17,28), retained plant sterols in the liver probably lead to higher absolute serum concentrations and their ratios to cholesterol. This led us to consider whether the ratio of cholestanol and plant sterols to cholesterol might be markers of cholesterol secretion into bile.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that UDCA also reduces biliary output of plant sterols and cholestanol. Since UDCA has no effects on lipoprotein metabolism (16,17,28), retained plant sterols in the liver probably lead to higher absolute serum concentrations and their ratios to cholesterol. This led us to consider whether the ratio of cholestanol and plant sterols to cholesterol might be markers of cholesterol secretion into bile.…”
Section: Discussionmentioning
confidence: 99%
“…A rate of 24-38% has been reported for treatment with UDCA alone [54,55]. Although UDCA and CDCA share a common mechanism of action (i.e., increasing the solubility of cholesterol in bile) [56], the safety and efficacy of UDCA are reported to be superior [57,58]. Since CDCA was shown to cause diarrhea at a relatively high frequency and possibly have transient effects on liver dysfunction and serum lipid levels, its use in general clinical practice has decreased [59].…”
Section: Commentarymentioning
confidence: 99%
“…First, fecal fatty acid analyses indicate that exogenous bile acids cause a decrease in the proportion of long chain saturated fatty acids in short bowel syndrome patients ( 408 ). Second, administration of cholestyramine to rats causes selective malabsorption of long chain saturated Europe which showed that CDCA had unequivocal efficacy and minimal toxicity ( 424,425 ).…”
Section: Gallstone Dissolution By Oral Bile Acidsmentioning
confidence: 99%